Knowledge and attitude of some Nigerian dentists concerning the use of space maintainers in Dentistry - A. T. Adeyemi; O. O. Denloye; O. O. Bankole (Nigerian Dental Association, 2007)
Objective: This study was carried out to determine the knowledge and attitude of some Nigerian dentist concerning the use of space maintainers in dentistry. Method: Structured and self administered questionnaires were sent to 60 dentists in Ibadan and Ile -Ife towns in the South - West region of Nigeria. Information required include respondent\'s biodata, year of graduation, specialty, knowledge of space maintainer, how often it is recommended, reasons for not recommending, and the types usually recommended. Result: Forty Six (70.6%) dentists comprising 63% females and 37% males responded to the questionnaire. All respondents were familiar with space maintainers but 28 (60.8%) claimed that they had never recommended it before. A number of reasons were given for not recommending space maintainers Fifty percent (50%) of those who had never recommended claimed that there was no orthodontic technician to fabricate it and that it was an expensive procedure, 39.2% claimed it was due to lack of appropriate dental materials needed for its fabrication, 7.1% claimed that the children may not cooperate and 7.1% claimed that parents did not want it for their children. The commonest space maintainer used by the dentists was the removable partial denture (71.8%) followed by Band and Loop (28.2%). None used lingual arch and distal shoe. Conclusion: The most commonly used space maintainer in this environment is the removable partial denture. All 46 dentists agreed that space maintainers help in preventing malocclusion and subsequently agreed to recommend space maintainers if the required materials were available and whenever it was necessary to do so.